SOLUTIONS FOR SOFT SKILL TRAINING FOR STUDENTS IN VIETNAM TODAY - Thi, Hue Tran (IJRDO- Journal of Educational Research, 2023)
In higher education, with the current context of globalization and international integration, equipping students with soft skills (soft skills) has become very important and necessary. The impact of many information flows, many cultural flows has affected the awareness, attitude and behavior of young people. For students of pedagogical schools, soft skills play an even more important role stemming from the professional characteristics of the sector. The output of students in pedagogical schools is mainly related to teaching - a field that requires ingenuity, flexibility, flexibility, skills in interaction, communication, and problem solving. To meet this goal, pedagogical schools need to attach importance to the education of soft skills for students in the training process. Because soft skills is not determined by the personality of the individual, but is formed, developed and increasingly perfected through the process of learning and training. Factors affecting the management of soft skill training for students of pedagogical schools in Vietnam